Penerapan Metode Design Thinking dan User Experience Questionnaire (UEQ) dalam Perancangan User Interface E-Learning - Kusuma, M. Bagus Aria; Sartika, Dewi; Ramadhan, Mustafa (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
E-learning is a teaching and learning medium that is carried out via a computer connected to the internet. E-Learning can replace all the facilities available at the place of learning. Interactions carried out by users give rise to various perceptions. This relates to the User Interface and User Experience, if a platform does not meet adequate user experience aspects, such as content that is less familiar and does not meet user expectations. This study aims to design an E-learning user interface so that it can create a design that meets user expectations and makes it easier for users to carry out online learning activities using the design thinking method. The results of design measurements using the User Experience Questionnaire (UEQ) method get an average score on the Attractiveness scale with a value of 1.80, Efficiency with a value of 1.67, Dependability with a value of 1.51, Stimulation with a value of 1.62, and Novelty with a value of 1 .13 with the benchmark category